The Role of Celebrity Endorsement, Brand Image, Customer Review with Emotional Marketing as an Intervening for Noera's Purchase Decision - Putri, Dewa Ayu Mutiara Pradnyamitha Sedana; Gorda, A.A.N. Oka Suryadinatha (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this study was to determine the effect of Celebrity endorsement on Emotional Marketing, to determine the effect of Brand Image on Emotional Marketing, to determine the effect of Customer Review on Emotional Marketing, to determine the effect of Celebrity endorsement on Purchasing Decisions, to determine whether the effect of Brand Image on Purchasing Decisions, to determine whether the effect of Customer Review on Purchasing Decisions, to determine whether the effect of Emotional Marketing on Purchasing Decisions. The types of data used in this study are quantitative and qualitative. The results showed that the relationship between celebrity endorsement on emotional marketing was positive and significant. The relationship between brand image and emotional marketing is positive and significant. The relationship between customer reviews on emotional marketing is positive and significant. The relationship between celebrity endorsement and purchasing decisions is positive and significant. The relationship between brand image and purchasing decisions is positive and significant. The relationship between customer reviews on purchasing decisions is positive and significant. The relationship between emotional marketing on purchasing decisions is positive and significant.